Rational design of coralloid Co9S8–CuS hierarchical architectures for quantum dot-sensitized solar cells. Issue 42 (16th October 2018) - Hong, Xiaodan; Liu, Qun; Gao, Xiaoyue; He, Chunfeng; You, Xingyan; Zhao, Xin; Liu, Xiangyang; Ye, Meidan
Abstract : Coralloid Co9 S8 –CuS hierarchical structures with high stability and remarkable electrochemical activity in QDSCs are firstly in situ grown on FTO substrates, which are also applicative on other flexible conductive substrates for potential applications in wearable devices. Abstract : Metal sulfide nanostructures, which have been widely studied in recent years, are one of the most promising candidates in energy devices. Herein, coralloid hierarchical structures composed of Co9 S8 hollow nanoneedle trunks and CuS nanosheet branches are, for the first time, well-constructed on fluorinated tin oxide (FTO) substrates via a multistep route. A seeding assistant strategy is applied to grow uniform and firm metal sulfide films on the FTO substrates. It is revealed that different seeds ( i.e., TiO2, CuS and ZnO) all have a positive effect to facilitate the film growth because of their surface roughening behavior on the FTO substrates. Significantly, such three dimensional (3D) Co9 S8 –CuS electrodes show superior electrocatalytic performance in the reduction reaction of polysulfide electrolyte, and yield an enhanced power conversion efficiency of 4.50% for CdS/CdSe quantum-dot sensitized solar cells as counter electrodes when compared with the one dimensional (1D) Co9 S8 hollow nanoneedle (3.25%) and two dimensional (2D) CuS nanosheet (3.83%) electrodes. More impressively, the coralloid structure exhibits excellent stability in the electrochemical cycling tests, keeping 80% current after 500 cycles. Above all, the synthesis strategy here is also feasible to fabricate hybrid Co9 S8 –CuS films on various flexible substrates, such as carbon cloth, Ti mesh, and Ni foam for potential applications in wearable energy devices.